2008
DOI: 10.1063/1.3002335
|View full text |Cite
|
Sign up to set email alerts
|

Environment-assisted quantum walks in photosynthetic energy transfer

Abstract: Underlying physical principles for the high efficiency of excitation energy transfer in light-harvesting complexes are not fully understood. Notably, the degree of robustness of these systems for transporting energy is not known considering their realistic interactions with vibrational and radiative environments within the surrounding solvent and scaffold proteins. In this work, we employ an efficient technique to estimate energy transfer efficiency of such complex excitonic systems. We observe that the dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
1,439
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 1,147 publications
(1,493 citation statements)
references
References 61 publications
32
1,439
2
3
Order By: Relevance
“…This finding mirrors the results found in the transport analysis of the FMO complex 9,16 and demonstrates that no fine-tuning of specific vibrational modes is required to sustain robust and efficient environmentally assisted energy transfer. 11,12,56 5 Chlb/Chla transfer time-scale in LHC II LHC II has been extensively studied within the Redfield, Förster, and interpolating approximations. Without an exact solution of the open system dynamics obtained with QMaster, the error made by the approximate methods is undefined and it is not known which approximation works best for a specific system.…”
Section: Influence Of the Vibrational Peaks On The Transport In Lhc IImentioning
confidence: 99%
See 1 more Smart Citation
“…This finding mirrors the results found in the transport analysis of the FMO complex 9,16 and demonstrates that no fine-tuning of specific vibrational modes is required to sustain robust and efficient environmentally assisted energy transfer. 11,12,56 5 Chlb/Chla transfer time-scale in LHC II LHC II has been extensively studied within the Redfield, Förster, and interpolating approximations. Without an exact solution of the open system dynamics obtained with QMaster, the error made by the approximate methods is undefined and it is not known which approximation works best for a specific system.…”
Section: Influence Of the Vibrational Peaks On The Transport In Lhc IImentioning
confidence: 99%
“…4 On top of the relaxation process, oscillatory components prevail in 2d-spectra which contain signatures of electronic coherences and specific vibrational modes. 6,[8][9][10] The coupling to the environment determines the transfer efficiency in LHCs 11,12 through the bath-correlation time of the phonon bath, [13][14][15] the shape of the continuum part of the spectral density, 9,16 and specific structures within the spectral density. 9,17 For the FMO complex, the superohmic character of the spectral density results in long-lasting electronic coherences despite a strong coupling to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Fenna-MatthewsOlson (FMO) complex, these coherences can persist on picosecond timescales in cryogenic conditions and are still observable at room temperatures [2,8]. Several phenomenological theories have subsequently shown that there is an optimal mixture of coherent inter-pigment energy transport and stochastic environmental noise that may lead to faster and higher-yield energy delivery in PPC architectures, suggesting that quantum effects may underpin their efficient function [9][10][11][12][13][14][15]. Microscopic investigations have also recently shown the key role of both discrete and continuous environmental fluctuation spectra in stabilising the long-lasting coherences observed in spectroscopy as well as facilitating efficient transport [16][17][18][19][20].…”
mentioning
confidence: 99%
“…The states obeying H S |e n = E n |e n are in general delocalized excitonic states, which can be also be expressed in the site basis as |e n = ∑ i C i n |i . The ultimate transfer of the exciton to a reaction center is modelled by including an isolated site (labeled 0 and referred to as the 'sink') which is populated irreversibly from a particular local site [9][10][11].…”
mentioning
confidence: 99%
“…In periodic systems, for example, the quantum particle propagates much faster (ballistic propagation) than its classical counterpart (diffusive propagation) [1]. Quantum walkers have been widely studied in a variety of different settings such as in the development of quantum algorithms [2][3][4], efficient energy transfer in proteins complex [5], classical optics [6,7], waveguide lattices [8,9], nuclear magnetic resonance [10], quantum dots [11], trapped atoms in optical lattices [12,13], disorder [14,15], interacting particles [16,17] and bacteria behavior in biological systems [18].…”
Section: Introductionmentioning
confidence: 99%